(untitled) (Analysis in Theory and Applications, 2014)
In this paper we propose the q analogues of modified Baskakov-Szász operators. We estimate the moments and establish direct results in terms of modulus of continuity. An estimate for the rate of convergence and weighted approximation properties of the q operators are also obtained.